List of grasshopper species (Orthoptera, Acridoidea) deposited at the Universidade Federal Rural de Pernambuco’s Entomological Collection - Almeida, Argus Vasconcelos de; Linares, Cristina Rojas de Andrade (SITIENTIBUS série Ciências Biológicas, 2010)
The grasshoppers deposited at the Entomological Collection of the UFRPE are represented by 35 samples, which are distributed in the five families: Romaleidae, Acrididae, Pyrgomorphidae, Pauliniidae and Omexechidae. The majority of the specimens were collected within Pernambuco State in 12 locatities, at three major areas: Mata, Agreste, and Sertão. There are also samples from other states such as Paraíba, Rio de Janeiro, Amazonas, Mato Grosso, and Rio Grande do Sul.